POLICE EFFORTS IN COUNTERING TRAFFIC OFFENCES (CASE STUDY OF PATI CITY POLICE TRAFFIC UNIT) - Cesardo, Muhammad Zaki (UNISSULA Semarang, 2024)
This research aims to find out the police efforts in overcoming the level of traffic violations, obstacles in overcoming the level of traffic violations and their solutions, as well as police efforts in overcoming the level of traffic violations in the future. This research uses a juridical sociological approach with descriptive analytical research specifications. The data collection method used is primary data obtained from field studies and secondary data obtained from interviews. The data analysis method uses qualitative analysis. Based on the research, it is concluded that the police efforts in overcoming the level of traffic violations are through preemptive efforts through socialisation activities in the school environment, to the general public, and to the automotive club community. Preventive efforts are carried out by guarding activities at guard posts and traffic arrangements in areas prone to traffic violations and patrol. Repressive efforts by taking action by giving warnings and ticketing using the ETLE system. The obstacles in overcoming the level of traffic violations faced by Sat Lantas Polresta Pati come from law enforcement factors, facility factors, community factors, and cultural factors. The solution to overcome these obstacles is to conduct socialisation of orderly traffic; instill a culture of orderly traffic; give polite and calm explanations to violators; notify the vehicle owner's tax has committed a violation and has blocked the STNK then asked to complete the payment of ticket fines and urged to immediately process the vehicle name change; the need for additional officers as well as increasing human resources and by using ETLE mobile and additional CCTV cameras on a number of roads in Pati Regency. Police efforts in overcoming the level of traffic violations in the future are by developing the Electronic Traffic Law Enforcement system and Traffic Attitude Record.